2018
DOI: 10.1186/s12865-018-0282-8
|View full text |Cite
|
Sign up to set email alerts
|

Variation in IL-21-secreting circulating follicular helper T cells in Kawasaki disease

Abstract: ObjectiveCirculating follicular helper T (cTfh) cells are a specialized subset of CD4+ T cells that express the CXC-chemokine receptor 5 (CXCR5). These cells exhibit immune activities by inducing B cell differentiation and proliferation via the secretion of interleukin (IL)-21. Multiple studies have demonstrated that cTfh cells are associated with the progression and severity of numerous diseases. To investigate the role of cTfh cells in the development of Kawasaki disease (KD), we analyzed the distinct subpop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Recently, researchers found the increased percentage as well as absolute number of CD19+ cells in the peripheral blood of patients with KD [12]. In addition to these direct evidence, our latest study presented an increased level of one activated subset of T follicular helper cells and serum IL-21 [13, 14], which are vital to B-cell proliferation and differentiation [15], strongly suggesting the involvement of humoral immunity in KD. Moreover, with the development of genomics, susceptible genes associated with B cells have also been identified [16].…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…Recently, researchers found the increased percentage as well as absolute number of CD19+ cells in the peripheral blood of patients with KD [12]. In addition to these direct evidence, our latest study presented an increased level of one activated subset of T follicular helper cells and serum IL-21 [13, 14], which are vital to B-cell proliferation and differentiation [15], strongly suggesting the involvement of humoral immunity in KD. Moreover, with the development of genomics, susceptible genes associated with B cells have also been identified [16].…”
Section: Introductionmentioning
confidence: 62%
“…One of the advantages for the differentiation of B cells into ASCs may be the elevation of B-cell-activating factor (BAFF), which can effectively promote the proliferation, differentiation, and survival of B cells [31]. Another superiority for ASCs is the increased levels of cytokines, such as IL-6, IL-17 and IL-21 [13, 32, 33]. Furthermore, increased expression of CD138 is capable of promoting the maturation, accumulation and particularly, survival of ASCs upon IL-6 signaling [34].…”
Section: Discussionmentioning
confidence: 99%
“…[ 7 ] Furthermore, according to our previous studies that included 24 KD patients without coronary involvement and 20 healthy controls, the percentages of CD4 negative subpopulation were 6.45% (2.99–14.5) and 6.87% (2.6–10.3), respectively, of circulating CXCR5+ T cells. [ 8 ] Thus, we believe that the levels of Tfc-like cells of the 2 patients in the acute stage are affirmatively increased.…”
Section: Discussionmentioning
confidence: 79%
“…A recent study showed that in patients with myositis, IL-21 expressing CCR7 lo PD-1 hi efficient cTfh cells significantly increased, and the frequencies of these cells had a correlation with the disease progression [ 28 ] . Moreover, the percentage of ICOS hi PD-1 hi efficient cells was higher in patients with Kawasaki syndrome [ 29 ] . The ICOS + PD-1 + cTfh cells and IL-21 producing CD4 + CXCR5 + PD-1 + T cells were also shown to be significantly higher in patients with Sjögren syndrome [ 30 ] .…”
Section: Discussionmentioning
confidence: 99%